Comparative study on the growth and productivity of Sesbania and leucaena in the Central Plateau region,Rewanda - Yamoah, C.F.; Eylands, V.J.; Akyeampong, E. (1992)
A study was conducted in the Central Plateau region of Rwanda to assess the productivity ofSesbania sesban and three Leucaena species in hedgerow intercropping systems. S. sesban grew and accumulated biomass most rapidly in the first 10 months of growth. During the following 6 months the fastest growth was observed in L. diversifolia (provenance Rwanda). After cutback, regrowth from S. sesban dropped whereas in the Leucaena species it increased. S. sesban produced more stakes than the Leucaena species at 10 months after planting but less at 16 months. Compared to the control, manuring and fertilization had a more pronounced effect on biomass yield than other measured parameters. Although farmers in the region prefer 5. sesban to Leucaena species because of its rapid initial growth, this study showed that, in terms of long-term productivity in alley cropping systems, Leucaena species hold considerable promise. Among the Leucaena species tested, the performance of L. leucocephala was inferior to L. diversifolia in all the parameters measured.